Societal Peace: The Elements of its Entrenching and the Impact on the Advancement of the Islamic Community - Keleibi, Yousef A.H (Journal of Islamic Sciences, 2019)
The creation a societal peace between all the components of the Muslim community is a demand that Islamic Sharia is sought to be achieved. The problem statement in the present study lies in the absence of societal peace culture by some Muslims, at the same time this issue is not clarification for its importance. Therefore, the Islamic Shariah sought to enhance and entrench due to its importance and as being one of Maqased al-Shariah. The study aims to demonstrate the importance of societal peace to the Muslim community and the mechanisms of the entrench, as well as show the implications on the creating of the societal peace in the Muslim community. The study followed the descriptive and analytical approach, through described the societal peace and security. Furthermore, description and analysis of the elements of societal peace and its impact on the Muslim community. The study concluded that one of the purposes of Islamic shariah is to establish the societal peace within the Muslim community, added to that the presence of factors considers one of the elements of the consolidation of community peace. Lastly, the study concluded that the societal peace is one of the cultural advancement factors and the situation is provided by the societal peace is contributed to progress, development and advancement.